A Critical Exploration of Effective Challenges and Opportunities in Digital Indonesian Language Learning: A Systematic Literature Review - Adam, Sumarlin; Pateda, Lamsike; Solihin, Iramadhana; Ahmad, Nuraina; Meiarni, Ita (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
Digital transformation in Education has brought significant implications to Indonesian learning practices, but still leaves complex conceptual, technological, and pedagogical challenges. This research aims to systematically explore the challenges and opportunities in the implementation of digital-based Indonesian learning, as well as evaluate the impact of digital platforms on motivation, language skills, and the effectiveness of learning tools. This study uses the Systematic Literature Review (SLR) method with a qualitative thematic synthesis, based on 10 selected articles published between 2020 and 2025. The literature selection process follows the PRISMA 2020 flow, and data analysis involves manually extracting key findings from each study. The results of the study show that the main challenges include low teacher digital literacy, a lack of integration of technology pedagogy, student unpreparedness in independent learning, and limited digital access and inclusivity. On the other hand, opportunities include using technologies such as virtual reality, gamification, machine learning, and interactive media to increase motivation and learning engagement. This study concludes that digital Indonesian learning requires a multidimensional theory-based approach to create an adaptive, inclusive, and transformative learning system.